The effect of aquatic and land exercises on pain, health related quality of life, kinesiophobia and disability in chronic low back pain: A randomized clinical trial - Nilay Çömük Balci; Ayça Aytar; Emine Atici; Gülşen Taşkin; Mustafa Gülşen; Mert Demirsoz (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Background: This study aims to compare the effectiveness between aquatic exercise interventions and land-based exercises in the treatment of Chronic Low Back Pain.  Methods: Thirty patients were randomly allocated to land exercise (n=15) and aquatherapy group (n=15). Both groups underwent Hot pack, conventional TENS, and continuous ultrasound. A water-based exercise program was conducted in the aquatherapy group for 15 patients in an indoor swimming pool. The land-based exercise program included abdominal and back strengthening exercises. All assessments were done before and after the treatments (4th week). The pain and functional status of patients were evaluated.  Results: There were no statistically significant differences in the demographic features between groups. The pre and post-therapy differences between groups showed no significant results between groups in VAS, MODI, TAMPA, and the standardized SF-36 (p>0.05).  There was a significant improvement in SF-36 role-emotional score in the land exercises group compared to aquatic exercises (p ≤ 0.05). The pre and post-therapy differences within groups showed a significant decrease in VAS score in aquatic exercises group (p<0.05), a similar observation was noted in the land exercises group too (p<0.05). There was also a significant decrease in ODI, TAMPA, and the physical functioning component of SF-36 in land exercises group.  Conclusions: The findings from this study show similar benefit of aquatic exercises and land exercises on pain, disability, health related quality of life and kinesiophobia in chronic low back pain, even land exercises has significant effect in emotional role domain of health-related quality of life.